2021
DOI: 10.1093/eurjcn/zvab094
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram monitoring in the prone position in coronavirus disease 2019 acute respiratory distress syndrome

Abstract: Aims Prone positioning is increasingly used for treating coronavirus disease 2019 (COVID-19)-induced acute respiratory distress syndrome (ARDS). In these high-risk patients for cardiovascular events who may spend more than 16 h a day in the prone position, an adequate monitoring of electrocardiogram (ECG) is mandatory. However, effects of prone positioning on the ECG are unknown as is the validity of the ECG recorded with electrodes placed dorsally. We aimed to compare ECG data obtained in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…9 The difference in QT and PR intervals between these 2 ECG modalities is controversial. 6,7,10 Moreover, the prone ECG may cause STsegment elevation of the anterior chest, which results in precordial leads being neglected. 6 At present, the diagnostic criteria for STEMI are based on a supine ECG of at least 2 contiguous leads with ST-segment elevation of at least 1 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The difference in QT and PR intervals between these 2 ECG modalities is controversial. 6,7,10 Moreover, the prone ECG may cause STsegment elevation of the anterior chest, which results in precordial leads being neglected. 6 At present, the diagnostic criteria for STEMI are based on a supine ECG of at least 2 contiguous leads with ST-segment elevation of at least 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Intervals: QRS durations in the prone position are significantly shorter than those in the supine position . The difference in QT and PR intervals between these 2 ECG modalities is controversial . Moreover, the prone ECG may cause ST-segment elevation of the anterior chest, which results in precordial leads being neglected …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the comparable trending ability of esCCO with that of TEE, esCCO is noninvasive and easily accessible. A recent study revealed an excellent correlation between the ECG parameters in the supine and prone positions when detecting the QRS axis, PR, RR, QRS, and QT intervals with electrodes placed on the torso and dorsal aspect [23]. In addition, since the distance from the heart to the fingertip, where the upstroke of pulse oximetry is detected, does not change according to the patient's position, the prone position does not influence the quality of PWTT and esCCO.…”
Section: Discussionmentioning
confidence: 97%
“…Judging from a previous study [23] and the principle of the esCCO system, the prone position itself may not interfere with the ability of esCCO to estimate CO. Further studies should determine the ability of esCCO under different circumstances as it may be useful and feasible for continuous monitoring CO in other noncardiac surgeries performed in the prone position.…”
Section: Discussionmentioning
confidence: 99%
“…54 Finally, the reduction in magnitude of QRS complexes on surface electrocardiography in PP suggests a reduction in cardiac volume and an increase in PR length linked to a better venous return. 55…”
Section: Hemodynamic Effectmentioning
confidence: 99%